Competing nuclear weapon development in South Asia: India and Pakistan - Muhammad Syafiq, Abdullah (2015)
This study is an attempt to explore the main factors that influence competing nuclear weapons development in South Asia. There are only two countries who possessed nuclear weapon in South Asia. Both Pakistan and India’s relation in economy are good especially in trade activities. However, the relation is different when it comes to security aspect. Therefore, the purpose of this study is to examine the factors that led them to weaponize their nuclear power in South Asia with particular focus on India and Pakistan with special emphasis on the development of nuclear weapon in both states. Finally, this study will recognize the implications on relationship between India and Pakistan in terms of nuclear weapon development.